Covid19 Drug Efficacy Statistical Analysis. Issue 1 (March 2021) - Zhang, Xuerong; Zhu, Qinyu; Qiang, Jiaying; Shen, Jiaming
Abstract: Recently, a new SARS-CoV-2 coronavirus named COVID 19 sparked panic worldwide. More than 1000 ongoing therapeutics were dealing with it. However, the efficacy of these treatments was still fuzzy. In this paper, we analyzed 4 main types of treatments individually and mutually based on clinical trials data. T-test, models like COX and GEE logistic regression are adopted to evaluate the efficacy.